Athenian University Students on Facebook and Privacy: A Fair "Trade-Off "?. (July 2016) - Papathanassopoulos, Stylianos; Athanasiadis, Elias; Xenofontos, Maria
This article explores how Athenian university students "manage" their privacy on Facebook while socially interacting with other users. Survey data of undergraduate students in Athens reveal that the social network site use "validates" and enhances the pre-existing social context and that the relationship level has an impact on the way users contact other users on it. We find that Facebook users feel that they are able to use most of the privacy settings to protect their personal data. Yet, they are concerned about the disclosure of their personal information which is perceived to be their primary responsibility. Despite these concerns, they appear to feel in control of their privacy through the abilities they are offered by the social networking site (SNS). We also argue that even if they realize that they are disclosing their personal information, this doesn't cause a great deal of insecurity.